The role of LMX and followership in strategy implementation : A case study from IT project teams - Sopanen, Elina (My University, 2026)
The purpose of this master’s thesis is to examine the relationship between leader-member exchange (LMX), followership, and strategy implementation in IT project teams of an international organization. The organization has gone through significant changes in recent years, especially in terms of the digital service development. As part of these changes, IT projects have become more important for operational activities and the implementation of strategic goals. The aim of this research is to explore how the relationship between a leader and an employee is related to active followership behaviour, and how these factors support the transition of strategic goals into daily project work. The theoretical framework of the study is built around LMX, followership, and strategy implementation literature. Previous studies and literature help to understand that the relationship between a leader and an employee is an interactive process, and that employees’ own, active behaviour can support the implementation of strategic goals in IT project teams. The research was conducted as a quantitative case study in an international logistics, e- commerce, and service organization. The data was collected from the organization’s IT project teams using an online questionnaire, which resulted in 52 responses. The questionnaire included statements measuring LMX, followership, and the implementation of strategy in daily work. The data was analysed using statistical methods including descriptive statistical analysis, reliability analysis, correlation analysis, and regression analysis. The results showed that both high-quality leader-member relationships and proactive followership behaviours were positively related to strategy implementation. However, followership and follower behaviour had a stronger connection to strategy implementation than leader-member relationships. The results suggest that strategy implementation is not only based on leadership, but that employee activity, actions, and commitment play a key role in implementing strategic goals into daily work. This research complements previous studies by emphasizing the importance of followership in strategy implementation in projects and by highlighting the connection between interactive leadership processes and the practical implementation of strategic goals. The findings also provide practical insights for organizations that seek to strengthen the strategy implementation in project teams.

Tämän pro gradu -tutkielman tarkoituksena on selvittää leader-member exchange (LMX) - suhteiden, seuraajuuden (followership) sekä strategian implementoinnin välistä yhteyttä kansainvälisen organisaation IT-projektitiimeissä. Organisaatio on viime vuosien aikana kokenut merkittäviä muutoksia erityisesti digitalisten palveluiden kehittämisen osalta. Osana tätä muutosta, IT-projekteista on tullut yhä tärkeämpiä operatiivisen toiminnan sekä strategisten tavoitteiden toteutumisen kannalta. Tämän tutkimuksen tavoitteena on tarkastella miten johtajan ja työntekijän välinen suhde liittyy aktiiviseen seuraajien käyttäytymiseen, sekä miten nämä tekijät tukevat strategisten tavoitteiden siirtymistä osaksi päivittäistä IT projektityötä. Tutkimuksen teoreettinen viitekehys rakentuu LMX- teorian, seuraajuuden sekä strategian implementointia käsittelevän kirjallisuuden ympärille. Aikaisemmat tutkimukset ja kirjallisuus auttavat ymmärtämään, että johtajan ja työntekijän välinen suhde on vuorovaikutteinen prosessi, ja työntekijöiden oma, aktiivinen toiminta voi tukea strategisten tavoitteiden toteutumista työtehtävissä. Tutkimus toteutettiin kvantitatiivisena tapaustutkimuksena kansainvälisesti toimivassa logistiikka-, verkkokauppa- ja palveluorganisaatiossa. Aineisto kerättiin sähköisellä kyselylomakkeella organisaation IT-projektitiimeiltä (N=52). Kysely sisälsi LMX-suhteita, seuraajuutta sekä strategisten tavoitteiden toteutumista päivittäisessä työssä mittaavia väittämiä. Aineisto analysoitiin tilastollisin menetelmin hyödyntäen kuvailevaa tilastoanalyysia, reliabiliteettianalyysiä, korrelaatioanalyysia sekä regressioanalyysia. Tulokset osoittivat, että sekä laadukkaammat LMX-suhteet että seuraajien käyttäytyminen olivat positiivisesti yhteydessä strategian implementointiin. Huomattavaa on kuitenkin, että seuraajuudella ja seuraajien käyttäytymisellä oli vahvempi yhteys strategian implementointiin kuin LMX-suhteilla. Tulokset viittaavat siihen, että strategian toteutuminen ei perustu pelkästään johtamiseen, vaan työntekijöiden aktiivisuudella, aloitteellisuudella ja sitoutumisella on keskeinen rooli strategisten tavoitteiden sisällyttämisessä osaksi päivittäistä työtä. Tämä tutkimus täydentää aiempia tutkimuksia korostamalla seuraajuuden merkitystä strategian implementoinnissa projekteissa, sekä tuomalla esiin vuorovaikutteisten johtamisprosessien yhteyden strategisten tavoitteiden käytännön toteutumiseen. Tulokset tarjoavat myös käytännön näkökulmia organisaatiolle, jotka pyrkivät vahvistamaan strategian implementointia projektitiimeissä.
Keywords: supervisor-employee relationship; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business